2019
DOI: 10.1021/acs.jcim.9b00798
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models Based on Molecular Fingerprints and an Extreme Gradient Boosting Method Lead to the Discovery of JAK2 Inhibitors

Abstract: Developing Janus kinase 2 (JAK2) inhibitors has become a significant focus for small-molecule drug discovery programs in recent years because the inhibition of JAK2 may be an effective approach for the treatment of myeloproliferative neoplasm. Here, based on three different types of fingerprints and Extreme Gradient Boosting (XGBoost) methods, we developed three groups of models in that each group contained a classification model and a regression model to accurately acquire highly potent JAK2 kinase inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…We want to emphasize that the substituent matching is just an ative way to evaluate the structural similarity;awide array of molecular features (i.e. molecular fingerprints, [43] molecular descriptors in RDKit, [20] physical organic descriptors, [16,17c,e] etc.) can be utilized to identify the related data for the designed hierarchical learning strategy based on the application purposes (vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We want to emphasize that the substituent matching is just an ative way to evaluate the structural similarity;awide array of molecular features (i.e. molecular fingerprints, [43] molecular descriptors in RDKit, [20] physical organic descriptors, [16,17c,e] etc.) can be utilized to identify the related data for the designed hierarchical learning strategy based on the application purposes (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…Through random splitting,90%of the related dataset awas used as training set, and the test set includes the other 10 %. A wide array of molecular descriptors based on 2D topological structure (i.e.R DKit [20] descriptors,M F, [43] etc. )o r3 D coordinate (i.e.A CSF, [44] MBTR, [45] etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Rather than searching for similar molecules, machine learning models are trained to predict the activities of molecules based on their fingerprints. [8][9][10][11] This bypasses the need for similarity search but these approaches still rely, at its core, on precalculated fingerprints. A new class of ML algorithms, called Graph Neural Networks (GNN) are thought to overcome the calculation of fingerprints.…”
Section: Introductionmentioning
confidence: 99%
“…All docking poses were ranked according to their docking scores, in which lower score indicated lower binding energy. Structure-based docking methods rank molecules via a scoring function that is calculated based on their inner methods (Yang et al, 2019). In addition, the previous study also showed that AutoDock Vina was a more efficient option for stimulating protein docking with macrolides and analogues of intermediate size ligand compared to other docking programs, such as Glide 6.6, AutoDock 4.2 and DOCK 6.5 (Castro-Alvarez et al, 2017).…”
Section: Resultsmentioning
confidence: 99%